The pout-pout fish - Diesen, Deborah; Hanna, Dan (New York : Farrar Straus Giroux, 2013)
The pout-pout fish believes he only knows how to frown, but one day a fish comes along that shows him otherwise.
On board pages.
Ages 1-2.
NP
Accelerated Reader AR
Keywords: Fishes -- Juvenile fiction; Marine animals -- Juvenile fiction; Friendship -- Juvenile fiction; Attitude (Psychology) -- Juvenile fiction